MicroRNA 449a can Attenuate Protective Effect of Urokinase Against Pulmonary Embolism - Zhu, Ran; Qi, Wei-yi; Liu, Ting-wei; Liu, Fan (Frontiers in Pharmacology, 2022)
Acute pulmonary embolism (APE) is a disabling diseases with high incidence rate and mortality rate. Although with high specificity, D-Dimer lacks specificity to assess APE, hence additional diagnostic and prognostic biomarkers are necessary. APE is widely treated with serine protease urokinase or urokinase-type plasminogen activator (uPA), which act as a catalyst for conversion of plasminogen to plasmin to resolve blood clots. However, it is unknown the role of differential expression of microRNAs (miRNAs) in protective effect of uPA against APE. Hence, we performed miRNA profiling in a hypoxia/reoxygenation (H/R) model of bronchial epithelial BEAS-2B cells in vitro and a APE mice model in vivo. Our analysis revealed that miR-34a-5p, miR-324-5p, miR-331-3p are upregulated with H/R or APE induction, whereas miR-429, miR-491-5p, and miR-449a are downregulated. The differential expression of the miRNAs was attenuated to levels comparable to control by treatment with uPA both in vitro and in vivo. In situ target prediction and analysis of potential functions of the target genes showed that the enrichment of biological processes and pathways were related to cell growth, proliferation, and inflammation. Ectopic overexpression of miR-449a using a mimic completely attenuated the protective effect of uPA in the H/R model in vitro. These results provide a group of miRNAs that could be used as markers, and the modulation of these miRNAs might have potential therapeutic benefits in patients with APE, which need to be validated in additional studies in humans.